Food price pass-through in the euro area The role of asymmetries and non-linearities - Gianluigi Ferrucci; Rebeca Jiménez-Rodríguez; Luca Onorante (European Central Bank (ECB), 2010)
In this paper we analyse the pass-through of a commodity price shock along the food price chain in the euro area. Unlike the existing literature, which mainly focuses on food commodity prices quoted in international markets, we use a novel database that accounts for the role of the Common Agricultural Policy in the European Union. We model several departures from the linear pass-through benchmark and compare alternative specifications with aggregate and disaggregate food data. Overall, when the appropriate dataset and methodology are used, it is possible to identify a significant and longlasting food price pass-through. The results of our regressions are applied to the strong increase in food prices in the 2007-08 period; a simple decomposition exercise shows that commodity prices are the main determinant of the increase in producer and consumer prices, thus solving the pass-through puzzle highlighted in the existing literature for the euro area.
Keywords: C32; C53; E3; Q17; 330; food commodity prices; inflation; non-linearities; Pass-Through; Lebensmittelpreis; Agrarpreis; Inflation; Regressionsanalyse; Eurozone; EU-Staaten